2022
DOI: 10.1108/ijse-06-2021-0332
|View full text |Cite
|
Sign up to set email alerts
|

Natural resource effect on child health outcomes in a multifactor health production model in developing countries

Abstract: PurposeThis study investigates if wealth from natural resources impacts child health in developing countries.Design/methodology/approachThe methodology includes testing the effect of rents from natural resources on under-five mortality rates using a multifactor health production model for 57 developing nations. The panel estimation procedure was applied to data covering 2002 to 2017, disaggregated by non-renewable and renewable resources and low and medium human development countries.FindingsThe results provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…Ref. [43] explored the impact of NRs on HD, fixating on child health in developing countries. The author convincingly demonstrated that wealth derived from total NRs is unrelated to reductions in under-five mortality rates.…”
Section: Resource Endowments and Human Well-being Nexusmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [43] explored the impact of NRs on HD, fixating on child health in developing countries. The author convincingly demonstrated that wealth derived from total NRs is unrelated to reductions in under-five mortality rates.…”
Section: Resource Endowments and Human Well-being Nexusmentioning
confidence: 99%
“…It is believed that improved NRs increase the well-being of a nation's population, although this may be equally environmentally harmful [47,52,59]. In addition, increased incomes from NRs could stimulate HW while also stimulating rent-seeking behavior [43,44,46]. Furthermore, NR abundance may reduce household incentives to educate children and the emphasis of governments on education, further crowding out human capital [24].…”
Section: Research Design and Datamentioning
confidence: 99%
“…Thus, less attention has been focused on the connection between NRR and LEX. Recent empirical data analysis from different jurisdictions has tried to connect NRR dependency to various indices of LEX and health outcomes [ 45 , 46 ]. Accordingly, this study examines the effect of NRR on LEX among the MINT nations.…”
Section: Introductionmentioning
confidence: 99%